Tracing organic matter sources in a tropical lagoon of the Caribbean Sea. (15th September 2017) - Alonso-Hernández, Carlos M.; Garcia-Moya, Alejandro; Tolosa, Imma; Diaz-Asencio, Misael; Corcho-Alvarado, Jose Antonio; Morera-Gomez, Yasser; Fanelli, Emanuela
Abstract: The natural protected lagoon of Guanaroca, located between Cienfuegos Bay and the Arimao River, Cuba, has been heavily impacted by human-induced environmental changes over the past century. Sources of organic matter in the Guanaroca lagoon and concentrations of radioisotopes ( 210 Pb, 226 Ra, 137 Cs and 239, 240 Pu), as tracers of anthropogenic impacts, were investigated in a 78 cm sediment core. Variations in total organic carbon (TOC), total nitrogen (TN), stable isotopic composition (δ 13 C and δ 15 N) and ratio of total organic carbon to total nitrogen (C/N) were analysed. On such a basis, environmental changes in the lagoon were revealed. Down core variation patterns of the parameters representing sources of organic matter were predominantly related to the impacts of human activities. Up to the nineteenth century, the principal sources of organic matter to sediments (more than 80%) were a mixing of terrestrial vascular plants (~48%) and freshwater phytoplankton (~8%), with minimal contribution from the marine component (~16%). In the period 1900–1980, due to the strong influence of human activities in the catchment area, the water exchange capacity of the lagoon declined substantially, as indicated by the relatively high proportion of organic matter originated from human activities (58%). Since 1980, as a result of management actions in the protected area, the lagoon has regained gradually its capability to exchange freshwater, showing sources of organic matter similar to the natural conditions recorded previous to 1900, although an indication of human impact (treated sewage contributed for 26% to the organic matter in sediments) was still observed and further management measures would be required. Highlights: Organic matter in the a Cuban lagoon were investigated in a sediment core dated. Cesium 137 and 239, 240 Pu were used for validate the 210 Pb dating. Stable isotopic composition (δ13C and δ15N) and Corg/N ratio were analysed. Important environmental changes in the lagoon were revealed in the last century. Changes in sources are mostly related to the impacts of human activities.